Insights into adaptive divergence of Japanese mantis shrimp Oratosquilla oratoria inferred from comparative analysis of full-length transcriptomes - Cheng, Jiao; Zhang, Liwen; Hui, Min; Li, Yuan; Sha, Zhongli (Frontiers in Marine Science, 2022)
The heterogeneous seascapes in the northwestern Pacific (NWP) can be important selective forces driving adaptive divergence of marine coastal species distributed along the gradients. Here, we tested this hypothesis in Japanese mantis shrimp (Oratosquilla oratoria) with a wide distribution in the NWP and a significant north-south population structure. To this end, the full-length (FL) transcriptomes of northern and southern O. oratoria were firstly sequenced using PacBio single molecule real-time sequencing technology. Based on the FL transcriptome data, we captured large-scale FL transcripts of O. oratoria and predicted the FL transcriptome structure, including coding region, transcription factor and long noncoding RNA. To reveal the divergence between northern and southern O. oratoria, we identified 2,182 pairs of orthologous genes and inferred their sequence divergences. The average differences in coding, 5’ untranslated and 3’ untranslated region were 1.44%, 2.79% and 1.46%, respectively, providing additional support to previous proposition that northern and southern O. oratoria are two species. We provided further evolutionary context to our analysis by identifying positive selected genes (PSGs) between northern and southern O. oratoria. In total, 98 orthologs were found evolving under positive selection and involved several environmentally responsive genes associated with stress response, immunity and cytoskeletal organization, etc. Furthermore, we found PSGs also diverged in gene expression response of northern and southern O. oratoria to heat stress. These findings not only highlight the importance of genetic variation in these genes in adapting to environmental changes in O. oratoria, but also suggest that natural selection may act on the plasticity of gene expression to facilitate O. oratoria adaptation to environmental gradients. Overall, our work contributes to understanding how marine coastal species has evolved to adapt to heterogeneous seascapes in the NWP.